Histopathological changes in the earthworm Eisenia andrei associated with the exposure to metals and radionuclides - Lourenço, Joana (2019)
Earthworms were exposed for 56 d to a contaminated soil, from an abandoned uranium mine, and to the natural reference soil LUFA 2.2. Histological changes in earthworm’s body wall (epidermis, circular and longitudinal muscles) and gastrointestinal tract (chloragogenous tissue and intestinal epithelium) were assessed, after 0, 14 and 56 d of exposure. Results have shown alterations in all the studied tissues after 14 d of exposure (except for the intestinal epithelium), yet more severe effects were registered after 56 d of exposure. Herein we report histopathological alterations as a good biomarker for the evaluation of soil quality. We also demonstrate that morphological changes in the body wall and gastrointestinal tract, are important endpoints that could be added to earthworm’s standardized tests, for the evaluation of soil toxicity, as part of the risk assessment of contaminated areas.